2017
DOI: 10.1016/j.juro.2016.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Interrater Reliability in Pediatric Urodynamic Tracings: A Pilot Study

Abstract: Faculty interpretations of urodynamic tracings showed only moderate agreement despite a close working relationship and similar training at a single institution. Variability in interpretation can strongly impact patient treatment. Therefore, further work is needed to standardize the reporting and interpretation of urodynamic studies to optimize patient care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…Furthermore, patients with high pressure bladders began an early treatment with CIC and anticholinergic drugs, which may have favored a better outcome. Finally, a study by Dudley et al showed that there exists a considerable variation between examiners in the performance of urodynamic studies, which may render different results (57).…”
Section: Risk Factors -Urodynamic Parametersmentioning
confidence: 99%
“…Furthermore, patients with high pressure bladders began an early treatment with CIC and anticholinergic drugs, which may have favored a better outcome. Finally, a study by Dudley et al showed that there exists a considerable variation between examiners in the performance of urodynamic studies, which may render different results (57).…”
Section: Risk Factors -Urodynamic Parametersmentioning
confidence: 99%
“…This becomes even more challenging if the formal interpretation of the tracing is left until after the urodynamics session is completed. As shown in several studies, and in an interactive presentation by Dr. Stacy Tanaka at the 2017 Spina Bifida Association meeting, the interpretation of the cystometrogram after the fact only increases the chances for greater inter-observer variability and possible intra-observer variability as well(1). In addition, after one has performed hundreds of studies, how can one begin to categorize the subsets of patients without looking at each record?…”
Section: Introductionmentioning
confidence: 99%
“…Overall, the clinical utility of UDS relies on the production of high-quality data that can be reproducibly interpreted between investigators. A 2017 study found weak inter-rater reliability in identifying detrusor overactivity and electromyographic synergy in children 17 . This finding echoes concerns regarding inter-rater reliability and protocol consistency in the ICS's Good Urodynamic Practice guideline 2 , which notes that this issue is not an inherent problem of the measurement itself but is rather a result of the current limitations of UDS equipment and the lack of a consensus on the precise method of measurement, signal processing, quantification, documentation and interpretation.…”
Section: Reproducibility and Standardizationmentioning
confidence: 99%
“…UDS is also used in certain paediatric urology scenarios, particularly in monitoring risk of renal deterioration in patients with neurogenic LUTD 17 . In 2015, the ICCS published guidelines for the use of UDS in children 16 .…”
Section: Current Trends In Urodynamicsmentioning
confidence: 99%